Studi Geologi Permukaan Daerah Bedingin dan Sekitarnya, Kecamatan Todanan, Kabupaten Blora, Jawa Tengah - Maezka Destanova Ramadhan; Muhammad Haikal Aldien Haq; Fawaz Maulana Juliansah; Keandra Rafif Haikal (Algoritma : Jurnal Matematika, Ilmu pengetahuan Alam, Kebumian dan Angkasa, 2025)
Bedingin area located in Todanan District, Blora Regency, Center Java Province. Fisiography is included in Rembang Zone (Bemmelen, 1949) which is a structural area. The purpose of this reasearch is to determine the distribution of lithology, geomorphology condition, and geology structures to provide geological information in this area. The research method used is a field survey with a mapping area of 5 x 5 Km2, there are 4 samples taken and analyzed with petrographic. As a results of the field survey, geomorphological, lithological types, and geological structure conditions in this area. The geomorphological of the research location is divided into Structurally Dense and Structurally Dense Hills. Lithologic types found from old to young are Quartz Sandstone of Ngrayong Formation, Mudstone of Bulu Formation, Claystone of Ledok Formation, and Packestone of Wonocolo Formation. The geological structures were found are Thrust Fault N176°E/20°, Strike-slip Fault N20°E/80°, and some indications of anticlines and synclines.